Criminal Liability of Midwives Perpetrators of Illegal Abortion Study Decision Number 131/Pid.Sus/2016/Pn.Kpg - Sigar P. Berutu; Setti Sri Ayu Malau; Rut Marsela Surbakti (Ekasakti Journal of Law and Justice, 2026)
This study examines the criminal liability of midwives who commit illegal abortions through a normative juridical analysis of Decision Number 131/Pid.Sus/2016/PN.Kpg. The three main issues studied include the legal regulation of the crime of illegal abortion by midwifery personnel, the fulfillment of the elements of criminal responsibility of the defendant, and the proportionality of the punishment imposed from the purpose of the crime and the principle of justice in Indonesian criminal law. This study uses a normative juridical method that is descriptive and analytical with a legislative approach, a conceptual approach, and a case approach. The results show that the Indonesian legal system has established a comprehensive normative framework in prohibiting the practice of illegal abortion by midwives, but inconsistency in law enforcement is its main weakness. All elements of the defendant's criminal responsibility were fulfilled conclusively, including the ability to be responsible, intentional in three grades, and the absence of a reason for criminal expungement. However, the three-month prison sentence imposed was considered disproportionate because the mitigating circumstances considered by the judge contained conceptual confusion and the construction of the indictment in the form of alternatives also contributed to the outcome of the sentence that was far from ideal, thus systemically weakening the effectiveness of the criminal law as an instrument to prevent the practice of illegal abortion by midwifery personnel in Indonesia.